THE USE OF DIGITAL TECHNOLOGIES, ESPECIALLY GEOGEBRA FOR TEACHING GEOMETRY: A SYSTEMATIC LITERATURE REVIEW - Maia, Lucas Emanuel de Oliveira (2022)
The objective of the work is to present a mapping of studies that approach the Use of Digital Technologies, especially GeoGebra for the Teaching of Geometry, using a Systematic Review of Literature (RSL). For the bibliographic research, works published between 2011 and 2020 were used from four digital repositories - SciELO, Google Scholar, Capes Periodical and RENOTE. This work had the study time interval from October 04, 2021 to November 30, 2021, in order to quantify and analyze the works that dealt with the Use of Digital Technologies for the Teaching of Geometry, to glimpse a review of the area. The analyzed studies demonstrate that the Use of Technologies, especially GeoGebra in the Teaching of Geometry is increasingly present in the educational context through various experiences.